Pengaruh Pemberian Berbagai Pupuk Kandang terhadap Tiga Varietas Pertumbuhan dan Hasil Tanaman Sawi (Brassica juncea L.): Effect of Application of Various Manures on Three Varieties of Growth and Yield of Mustard Greens (Brassica juncea L.) - Mira Hasra; Dewi Fithria (Perbal: Jurnal Pertanian Berkelanjutan, 2022)
Research on the effect of applying various manures on three varieties of growth and yield of mustard (Brassica juncea L.) was carried out in Arongan Village, Kuala Pesisir District, Nagan Raya Regency, starting from October to November 2021. The design used was a randomized block design (RAK) factorial. The first factor was manure which consisted of 3 treatment levels P0 (control/without manure), P1 (soil + cow manure 2:2), and P2 (soil + goat manure 2:1). The second factor was the variety which consisted of 3 treatment levels V1 (kumala variety), V2 (dora variety), and V3 (pakcoy variety). The results of the study did not show any interaction between the treatment of manure and varieties with all observed variables. The addition of manure had a significant effect on the number of leaves at 29 DAP and root length. Varieties treatment did not have a significant effect on all observed variables.